Uncovering the significance of CBX3 as an up-and-coming biomarker in cardio-vascular health - Muhammad Aamir Wahab; Nunzio Del Gaudio; Biagio Gargiulo; Vincenzo Quagliariello; Nicola Maurea; Michele Grieco; Rosaria Benedetti; Angela Nebbioso; Lucia Altucci; Mariarosaria Conte (Epigenetics Communications)
Abstract Cardiovascular disease (CVD) is the primary cause of mortality globally with a multifactorial etiology that involves epigenetics. Chromobox 3 (CBX3), the major isoform of heterochromatin protein 1, is involved in intricate epigenetic mechanisms affecting congestive heart failure. In patients with CVD affected by lung cancer risk, CBX3 exerts a sophisticated mechanism of action, suppressing the proliferation, migration, and formation of neointima in vascular smooth muscle cells (VSMCs) by affecting the Notch3 pathway, indicating a potential protective function against vascular remodeling and atherosclerosis. However, the broader im- pact of CBX3 on endothelial function, as well as its effects on monocyte/macro- phage and lymphocyte infiltration and function within the arterial wall, remain poorly understood. Since very little is known so far, more definite research would be needed to reveal the fine mechanisms of CBX3 action, along with its relationship in molecular processes and prospects as a biomarker. Specifically, CBX3 biological features could be examined to gain a greater insight into CVD risks. This review outlines the role of CBX3 in mechanisms associated with CVD and feasibility for optimizing pre-existing therapy and developing new therapeutic strategies based on personalized medicine.